Robust and high-performance soft inductive tactile sensors based on the Eddy-current effect - Wang,H; Kow,J; Raske,N; De,Boer G; Ghajari,M; Hewson,RW; Alazmani,A; Culmer,P (Sensors and Actuators A: Physical, 2017)
Tactile sensors are essential for robotic systems to interact safely and effectively with the external world, they also play a vital role in some smart healthcare systems. Despite advances in areas including materials/composites, electronics and fabrication techniques, it remains challenging to develop low cost, high performance, durable, robust, soft tactile sensors for real-world applications. This paper presents the first Soft Inductive Tactile Sensor (SITS) which exploits an inductance-transducer mechanism based on the eddy-current effect. SITSs measure the inductance variation caused by changes in AC magnetic field coupling between coils and conductive films. Design methodologies for SITSs are discussed by drawing on the underlying physics and computational models, which are used to develop a range of SITS prototypes. An exemplar prototype achieves a state-of-the-art resolution of 0.82mN with a measurement range over 15N. Further tests demonstrate that SITSs have low hysteresis, good repeatability, wide bandwidth, and an ability to operate in harsh environments. Moreover, they can be readily fabricated in a durable form and their design is inherently extensible as highlighted by a 4×4 SITS array prototype. These outcomes show the potential of SITS systems to further advance tactile sensing solutions for integration into demanding real-world applications.